Do “não comer” à anorexia: considerações sobre o sintoma no contemporâneo - Santos, Kyssia Marcelle Calheiros (2013)
In contemporary culture, while there is an excessive preoccupation with the body, there is eating symptoms emergence. Despite the previously existence of these symptoms, they were not that common and frequent in the clinic. Anorexia is considered one of these symptoms and according to that it was possible to question the relation betweenincreased anorexia incidence nowadays and idealization of thin body. The aimed of this study was to examine the relation between the cult of the body culture and anorexia in contemporaneity, reflecting on that context, if anorexia can be considered an analytical symptom. This work conducted a theoretical study, based on psychoanalysis. The method adopted was to read the texts more than once, from the researcher's encounter with the text, the purpose of producing a speech and not just the pursuit for the meaning of interpretative texts. So, it was used texts from Sigmund Freud, Jacques Lacan and authors that argue the binomials: body worship and contemporary culture, beauty codes and standards and anorexia, anorexia and ideal cultural;ideal body and ways / lifestyles; anorexia and symptoms. We also used two published clinical cases, to convey and intensifyconcepts, specifically anorexia, in psychoanalytic theory. It was observed that anorexia is presented differently nowadays, since there are individuals who participate in pro-anorexia movements and conceive it as a lifestyle. The anorexia exaltation is related to aspects of this culture and mostly with the idealization of thin body. In view of the increasing incidence of anorexia, it is understood that culture is not the cause but can propel this growth, since the constitution of the symptom is related to various life experiences of the subject. Accordingly, anorexia can only be considered an analytical symptom, from the encounter between analyst and patient. To do so, depends on the position of the subject to the treatment and the analyst’s intervention.